2022
DOI: 10.3390/cells11121866
|View full text |Cite
|
Sign up to set email alerts
|

hLMSC Secretome Affects Macrophage Activity Differentially Depending on Lung-Mimetic Environments

Abstract: Mesenchymal stromal cell (MSC)-based therapies for inflammatory diseases rely mainly on the paracrine ability to modulate the activity of macrophages. Despite recent advances, there is scarce information regarding changes of the secretome content attributed to physiomimetic cultures and, especially, how secretome content influence on macrophage activity for therapy. hLMSCs from human donors were cultured on devices developed in house that enabled lung-mimetic strain. hLMSC secretome was analyzed for typical cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Regardless of whether MSCs or their derivatives were used in the studies, their interplay with monocytes/macrophages is a key mechanism of therapeutic benefits [ 66 , 67 ]. As summarized in Table 1 , most studies found Mφ involvement in the beneficial effects of MSCs in lung injury or described a role for alveolar IL-10 increase in the effect.…”
Section: Mscs In Lung Injury Treatmentmentioning
confidence: 99%
“…Regardless of whether MSCs or their derivatives were used in the studies, their interplay with monocytes/macrophages is a key mechanism of therapeutic benefits [ 66 , 67 ]. As summarized in Table 1 , most studies found Mφ involvement in the beneficial effects of MSCs in lung injury or described a role for alveolar IL-10 increase in the effect.…”
Section: Mscs In Lung Injury Treatmentmentioning
confidence: 99%
“…As soon as cells are seeded in hydrogels they begin to remodel their microenvironment (Tjin et al, 2017;Martinez-Garcia et al, 2021b;Martinez-Garcia et al, 2022). Early reports of cells in lung ECM-derived hydrogels reflect findings in single component ECM hydrogels (Tjin et al, 2017), indicating that cells remodel the ECM in which they are embedded, and the nature of the ECM that they encounter directs these remodelling events (Nizamoglu et al, 2022b;Falcones et al, 2022). This fact makes the use of lung ECMderived hydrogels sourced from diseased lungs an ideal model to understand cellular responses within such a diseased microenvironment and to provide greater knowledge of the influence of the microenvironment to treatment effects.…”
Section: Lung Ecm-derived Hydrogels For Mimicking Cell:matrix Interac...mentioning
confidence: 99%
“…In particular, the physical signals exerted by the ECM composition, topography, and rigidity are translated to the cells via mechanotransduction which has been found to be crucial in regulating stem cell fate [1]. In contrast to traditional cultures, the biomechanical properties of hydrogels can be modulated to provide a physiomimetic 3D environment reproducing physiological and disease conditions in vitro [2][3][4][5]. The stemness and differentiation characteristics of mesenchymal stromal cells (MSCs) in decellularized ECM hydrogels are significant for stem cell therapy and for designing new treatments [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional cultures, the biomechanical properties of hydrogels can be modulated to provide a physiomimetic 3D environment reproducing physiological and disease conditions in vitro [2][3][4][5]. The stemness and differentiation characteristics of mesenchymal stromal cells (MSCs) in decellularized ECM hydrogels are significant for stem cell therapy and for designing new treatments [3,4]. Among the different opportunities and challenges, ECM-derived hydrogels are biomechanically tunable and have been recently used as MSCs delivery systems [6] and bioinks for 3D bioprinting [5] opening new possibilities for tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation